2011
DOI: 10.1080/10401334.2011.611763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Modified Longitudinal Simulation-Based Advanced Cardiovascular Life Support to a Traditional Advanced Cardiovascular Life Support Curriculum in Third-Year Medical Students

Abstract: Students in a modified longitudinal simulation-based ACLS curriculum demonstrated better proficiency in learning ACLS compared to a traditional curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…12 Similarly, for the American Heart Association's (AHA) Advanced Cardiac Life Support (ACLS) skills, no additional benefit of high-fidelity simulation was seen by some, 13,14 whereas others have found additional benefits of high-fidelity simulation. [15][16][17] One possible explanation for the discrepancy in these research findings could be that the relationship between fidelity and learning is dependent upon learner experience. 18 According to cognitive load theory, working memory is limited with respect to the amount of information it can hold and the number of operations it can perform on that information.…”
Section: Introductionmentioning
confidence: 69%
“…12 Similarly, for the American Heart Association's (AHA) Advanced Cardiac Life Support (ACLS) skills, no additional benefit of high-fidelity simulation was seen by some, 13,14 whereas others have found additional benefits of high-fidelity simulation. [15][16][17] One possible explanation for the discrepancy in these research findings could be that the relationship between fidelity and learning is dependent upon learner experience. 18 According to cognitive load theory, working memory is limited with respect to the amount of information it can hold and the number of operations it can perform on that information.…”
Section: Introductionmentioning
confidence: 69%
“… 9 , 10 Many medical school graduates feel underprepared and lack the confidence and skills to effectively participate in resuscitative efforts as interns beginning their residency programs. 10 14 The necessity for high-quality education of ACLS at the medical student level cannot be overstated. The integration of high-fidelity mannequin-based simulation (HFMBS) into existing ACLS curricula as a supplemental instructional tool has been advocated.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of high-fidelity mannequin-based simulation (HFMBS) into existing ACLS curricula as a supplemental instructional tool has been advocated. 10 , 15 – 21 A recent study of medical students using HFMBS in ACLS training showed significantly improved knowledge and psychomotor skills. 22 The costs associated with acquiring and maintaining an HFMB simulator may be impeding its use in many ACLS training programs.…”
Section: Introductionmentioning
confidence: 99%
“…Brennen4 demonstrated similar poor success rates to ours in the lay public. It is clear that interval training increases retention [1,[14][15][16]. Most studies did not look at specific skills within ACLS.…”
Section: Discussionmentioning
confidence: 99%